Biologia e taxonomia de trematódeos transmitidos por moluscos dulciaquícolas na represa da Pampulha, Belo Horizonte, Minas Gerais, Brasil - Hudson Alves Pinto (2013)
With the aim to increasing the knowledge about the life cycles of trematodes from Brazil, malacological surveys were carried out at Pampulha reservoir, Belo Horizonte, Minas Gerais, between January 2009 and November 2012. Cercariae were used to perform experimental infection studies and the developmental stages obtained were submitted to morphological analyses in order to taxonomic identification. A total of 32,576 specimens of snail from eight species (Biomphalaria glabrata, Biomphalaria straminea, Biomphalaria tenagophila, Lymnaea columella, Melanoides tuberculata, Physa acuta, Physa marmorata, Pomacea sp.) were examined, and 3,073 (9.43%) were found infected with larvae of 22 species of trematodes. Seasonal variation in species richness and percentage of infection by trematodes were observed, with higher values verified in dry seasons. Biomphalaria straminea was found harboring larvae of Apharyngostrigea sp. 1, Apharyngostrigea sp. 2, Austrodiplostomum compactum, Cercaria macrogranulosa, Clinostomum sp., Echinostomatidae gen. sp. 1, Echinostomatidae gen. sp. 2, Hysteromorpha triloba, Notocotylidae gen. sp., Paryphostomum segregatum, Petasiger sp., Ribeiroia sp., Schistosomatidae gen. sp., and Spirorchiidae gen. sp. 1. Biomphalaria glabrata was found infected with A. compactum, Clinostomum sp., Echinostomatidae gen. sp. 1, Echinostomatidae gen. sp. 2, P. segregatum, Ribeiroia sp., Spirorchiidae gen. sp., and Schistosoma mansoni. Cercariae of Clinostomum sp., Echinostomatidae gen. sp. 1, Echinostomatidae gen. sp. 2, and Spirorchiidae gen. sp emerged also from Biomphalaria tenagophila. Among the prosobranch mollusks, larvae of Centrocestus formosanus, Philophthalmus gralli and Renicola sp. emerged from Melanoides tuberculata, while xiphidiocercariae and Schistosomatidae gen. sp. 2 from Pomacea sp. Larvae of Echinostoma exile and Haematoloechidae gen. sp were found in P. marmorata and L. columella, respectively. In addition to the mollusks, potential second intermediate hosts were evaluated for natural infection with trematodes. Among fish, specimens of Poecilia reticulata were found infected with metacercariae of Apharyngostrigea sp., C. formosanus, Clinostomum sp., Posthodiplostomum nanum and Renicola sp.; Australoheros facetus with C. formosanus; Oreochromis niloticus with A. compactum, C. formosanus, Echinostomatidae gen. sp. and Ribeiroia sp.; Geophagus brasiliensis with Clinostomum heluans. Larval odonates (Orthemis discolor and Perithemis mooma) were found harboring metacercariae of Eumegacetes medioximus. In addition, a specimen of Striated Heron, Butorides striata, from the locality was found infected with Ascocotyle (Phagicola) angrense, Ascocotyle (Phagicola) pindoramensis, C. formosanus, C. heluans, C. marginatum, E. medioximus, P. nanum, and Prosthogonimus ovatus. New reports of the interaction between snails and trematodes were presented for the first time in Brazil and aspects of the life cycle of some of these parasites were elucidated.